Marx and Piaget: theoretical and epistemological approaches - Adrian Oscar Dongo-Montoya (Universidade Federal do Rio Grande do Sul, 2018)
The present paper aims at showing the closeness between Piaget's and Marx's thoughts concerning basic theory and epistemology issues of sociological research. Specifically, about the way both authors study the relation between these parts and the whole social aspects, the relation between the material action and social representation, the relation between sync and diachrony and finally the relation between scientific and ideological activities. In such perspective, it will be analyzed Piaget's studies regarding sociology and his agreement points with Marx's thesis. The results of such research prove the existence of real nearness between both thoughts and what was analyzed.